An approach to using humanitarian diplomacy to maintain sustainable agriculture in the conflict of Syria - Dede, Zıyad (Hasan Kalyoncu Üniversitesi Lisansüstü Eğitim Enstitüsü Siyaset Bilimi ve Uluslararası İlişkiler Ana Bilim Dalı, 2023)
This research focused on the relationship among humanitarian diplomacy, sustainable agriculture, and politics in conflict areas. Human diplomacy can be relied upon to promote sustainable agriculture through advocacy and influence over decision-makers in order to direct funding to more sustainable agricultural projects and thus achieve political stability. Agriculture is a mutual interest and common ground among the conflict actors in Syria. The ongoing conflict has caused a decline in the agricultural sector, but it still constitutes the backbone of the economy and a source of income for Syrian society. Support for this sector contributes to improving people's lives and mitigating ongoing conflict, and it will have a crucial role in post-conflict economic and social development. So, promoting sustainability in the agricultural sector through humanitarian diplomacy as an approach will contribute to conflict mitigation, migration mitigation, sustainable development, resisting climate change, and food security. The research was based on first-hand information gathered through interviews with Humanitarian local and international organizations, authorities, Politicians, and local councils involved in Syria's agricultural sector. Furthermore, the researcher's personal experiences and academic background are considered, as are field visits and observations, as well as secondary data analysis such as field reports, books, and academic journal articles. Many conclusions were drawn from the research, including the interdependence of politics and agriculture, as well as the interdependence of humanitarian diplomacy and politics in conflict zones. Aside from the role of humanitarian diplomacy in promoting peace and stability in conflict zones through sustainable agriculture, there are also challenges that humanitarian workers face in conflict zones, as well as the impact of politics on humanitarian aid. In the Syrian conflict, agriculture acts as a political mediator and humanitarian diplomacy is employed as soft power. Additionally, while political and humanitarian diplomacy can overlap and be used in conjunction, their respective focuses and goals are different. The study makes the following recommendations: emphasize agricultural policies and investments that support sustainable practices and raise awareness of the sustainability of agriculture among other conflict actors in Syria. A conflict-affected environment requires a sustainable approach to agriculture that takes into account both short-term requirements and long-term development. Collaboration and coordination among development actors, local government officials, and humanitarian organizations are critical. Humanitarian diplomacy and capacity building are essential skills for humanitarian organizations working in conflict zones. Sustainable agriculture should be included in a more comprehensive peacebuilding strategy that includes political dialogue, conflict resolution, governance reforms, and justice and reconciliation procedures.

Bu araştırma, savaş bölgelerinde insani diplomasi, sürdürülebilir tarım ve politika arasındaki ilişkiye odaklandı. Finansmanı daha sürdürülebilir tarım projelerine yönlendirmek ve böylece siyasi istikrarı sağlamak amacıyla karar vericiler üzerinde savunuculuk ve etki yoluyla sürdürülebilir tarımı teşvik etmek için insan diplomasisine güvenilebilir. Tarım, Suriye'deki çatışma aktörleri arasında ortak bir çıkar ve ortak zemindir. Devam eden çatışma, tarım sektörünün gerilemesine neden olsa da hâlâ ekonominin omurgasını ve Suriye toplumunun gelir kaynağını oluşturuyor. Bu sektöre verilen destek, insanların yaşamlarının iyileştirilmesine ve devam eden çatışmaların hafifletilmesine katkıda bulunmaktadır ve çatışma sonrası ekonomik ve sosyal kalkınmada çok önemli bir role sahip olacaktır. Dolayısıyla insani diplomasi yoluyla tarım sektöründe sürdürülebilirliğin teşvik edilmesi bir yaklaşım olarak çatışmaların azaltılmasına, göçün azaltılmasına, sürdürülebilir kalkınmaya, iklim değişikliğine direnmeye ve gıda güvenliğine katkıda bulunacaktır. Araştırma, Suriye'nin tarım sektöründe yer alan yerel ve uluslararası insani kuruluşlar, yetkililer, Politikacılar ve yerel konseylerle yapılan görüşmeler yoluyla toplanan ilk-elden-bilgilere dayanıyordu. Ayrıca araştırmacının kişisel deneyimleri ve akademik geçmişinin yanı sıra saha ziyaretleri; gözlemlerinin yanında saha raporları, kitaplar ve akademik dergi makaleleri gibi ikincil veri analizleri de dikkate alınır. Araştırmadan, siyaset ve tarımın karşılıklı bağımlılığının ile birlikte çatışma bölgelerinde insani diplomasi ve siyasetin karşılıklı bağımlılığı da dahil olmak üzere birçok sonuç çıkarıldı. Sürdürülebilir tarım yoluyla çatışma bölgelerinde barış ve istikrarın desteklenmesinde insani diplomasinin rolünün yanı sıra, insani yardım çalışanlarının çatışma bölgelerinde karşılaştığı zorlukların olduğu kadar siyasetin insani yardım üzerindeki etkisi de var. Suriye çatışmasında tarım siyasi bir arabulucu görevi görüyor ve insani diplomasi yumuşak güç olarak kullanılıyor. Ayrıca, siyasi ve insani diplomasi örtüşebilir ve birlikte kullanılabilir, ancak bunların odak noktaları ve hedefleri farklıdır. Çalışmada şu önerilerde bulunuluyor: Sürdürülebilir uygulamaları destekleyen tarım politikalarına ve yatırımlara ağırlık verilmesi ve Suriye'deki diğer çatışma aktörleri arasında tarımın sürdürülebilirliği konusunda farkındalık yaratılması. Çatışmalardan etkilenen bir çevre, hem kısa vadeli gereksinimleri hem de uzun vadeli kalkınmayı dikkate alan sürdürülebilir bir tarım yaklaşımını gerektirir. Kalkınma aktörleri, yerel yönetim yetkilileri ve insani yardım kuruluşları arasındaki işbirliği ve koordinasyon kritik öneme sahiptir. İnsani diplomasi ve kapasite geliştirme, çatışma bölgelerinde çalışan insani yardım kuruluşları için temel becerilerdir. Sürdürülebilir tarım, siyasi diyalog, çatışma çözümü, yönetişim reformları, adalet ve uzlaşma prosedürlerini içeren daha kapsamlı bir barış inşası stratejisine dahil edilmelidir.
Keywords: Humanitarian Diplomacy; Sustainable Agriculture; Politic